Oral health and Candida carriage in socioeconomically disadvantaged US pregnant women - Jin Xiao; Colleen Fogarty; Tong Tong Wu; Naemah Alkhers; Yan Zeng; Marie Thomas; Moustafa Youssef; Lin Wang; Lauren Cowen; Hossam Abdelsalam; Anna Nikitkova (BMC Pregnancy and Childbirth, 2019)
Abstract Background Despite the well-documented associations between poor maternal oral health and increased risk for adverse birth outcomes and dental caries in children after birth, prenatal oral health care is under-utilized, especially among the underserved population. In addition, oral Candida has recently been suggested as a potential culprit for children’s dental caries, with evident maternal contributions. Therefore, this study aimed to obtain epidemiological data on the oral health and oral Candida carriage in a cohort of underserved US pregnant women, and reveal factors associated with their oral Candida carriage. Methods Demographic-medical-oral hygiene practice data were collected. Comprehensive oral examination was conducted. Caries status and plaque index were recorded. Oral samples (saliva, plaque and swab) were processed to identify Candida species and Streptococcus mutans by culturing-dependent and -independent methods. Multiple logistic regression analyses were used to identify factors associated with oral Candida carriage and caries severity. Results Eighty-two socioeconomically disadvantaged women (48 pregnant and 34 non-pregnant) were enrolled. More pregnant women (79.1%) had > = 1 untreated decayed tooth when compared to their non-pregnant counterparts (47.1%) (p = 0.01). The average number of decayed teeth in pregnant and non-pregnant women was 3.9 and 3.1 (p > 0.05). Caries severity was positively associated with race (African American vs. white), plaque index and salivary Candida albicans level. C. albicans was the most predominant/abundant Candida strain, with cheek and tonsil as the most common colonized sites. The detection of C. albicans was 56%/56% in saliva and 40%/47% in plaque of the pregnant and non-pregnant groups, respectively. Study women’s oral Candida carriage is positively associated with hypertension [p = 0.03, odds ratio = 14.47(1.28, 163.51)], decayed teeth number [p = 0.04, odds ratio = 1.31 (1.01,1.69)] and salivary S. mutans level [p = 0.03, odds ratio = 4.80 (1.18–19.43)]. Conclusions Socioeconomically disadvantaged US women are in need of improved prenatal oral health, a large proportion of them have untreated decayed teeth and high carriage of oral Candida. Due to the observed significant association between the decayed teeth number and oral Candida carriage, providing oral health care during pregnancy (including limiting decayed teeth) will not only improve women’s oral health, but also present as a promising approach to reduce oral Candida carriage in women.